Developing A Digital Literacy Module To Enhance Elementary School Students’ Learning Motivation - Sudarjat, Jaja; Anwar, Wawan Syahiril; Suchyadi, Yudhie; Indriani, Rini Sri; Yusup, Muthia Khairunnisa P. (UNIVERSITAS PAKUAN, 2025)
The results of observations with several teachers at SD Islam Nurul Iman stated that students need stimulus so that students have adequate literacy skills. The purpose of the research is to develop digital literacy modules for elementary school students, test the feasibility of digital literacy modules, and determine the level of practicality of digital literacy modules applied in elementary school learning. The development research procedure uses the ADDIE (analyze, design, development, implementation and evaluation) model. The subjects of this study are students and classroom teachers of Nurul Iman Islamic Elementary School. The results of the study show that the module developed is in the form of a digital literacy module for elementary school students using the ADDIE model. The modules developed met the criteria were very valid with a percentage of 91.2% based on the assessment from the validators, the modules developed to students received a positive response and met the criteria very well with a percentage of 97%, while the results of the teacher's response received a positive response and met the very good criteria of 100% which can be used in learning.